QFD Methodology Application To 'UPM-Net': A Case Study. - Rizvi, S. Wasiul H. (2002)
Usability problems continue to offer a challenge to interactive system designers. One response has been an increasing emphasis on the role of users in design. The aim is to gain knowledge about users' work practice and the context of use of systems so as to achieve more effective designs. Experience has shown that it is a challenge to apply these techniques in practice, causing us to ask what are the special problems associated with involving users in design? The present work is planned to apply the QFD (Quality Function Deployment) technique to develop awareness of customers' needs. Quality Function Deployment (QFD) can be best described as a way of making the 'Voice of the Customer' throughout an organisation. It is a systematic process for capturing customer requirements and translating these into requirements that must be met throughout the 'supply chain'. The result is a new set of target values for designers, production people, and even suppliers to aim at in order to produce the output desired by customers. QFD is particularly valuable when design trade-offs are necessary to achieve the best overall solution because some requirements may conflict with others. QFD also enables a great deal information to be summarised in the form of one or more charts. These charts capture customer and product data gleaned from many sources, as well as the design parameters chosen for new product. In this way, they provide a solid foundation for further improvement in subsequent design cycles. In the present work, the system 'UPM-Net' was investigated by way of first identifying the specific users populations of the system, which are found to be of three types. One is the category of academic staffs, second one is of non-academic staffs and the third one is of students of UPM. Then the VOC: Voice of Customers was developed for which an inventory system in the form of questionnaire was evolved for collecting data from the end-user populations. The collected data were statistically analysed using SPSS (Statistical Package for Social Sciences), the results were obtained and discussed later in the light of the literature reviewed. The conclusions were based on such factors as connectivity, storage space needs, network features, technical services, user's features, and communication problems vis-a-vis UPM-Net. Finally, the scope for future research was presented. Thus one dimension of QFD i.e., VOC was established and it is hoped that such a study would help the people who are responsible for designing UPM-Net system in evolving a more user-friendly kind of UPM-Net system for future population of its end-users.